The Practicality of Dynamic Assessment in Reading Comprehension Strategies and Reading Motivation: Mirroring ESP Students\' Attitudes - Fatemeh Sharifi; Mehrdad Sepehri; sajad Shafiee (Iranian Journal of Educational Research)
Objective: This study investigated the effects of dynamic assessment (DA) on Iranian ESP university students' reading comprehension strategies and motivation. Furthermore, the views of Iranian ESP university students concerning DA were examined. Methods: This study employed a quasi-experimental methodology to recruit 80 Ph.D. students as the sample. The participants were separated into two groups: control (CG) and experimental (EG). Then, two questionnaires about metacognitive strategies and reading motivation (RM) were delivered to them. Following that, the sandwich style of DA was used to educate the EG to read psychological materials while the CG was trained in the traditional manner. After teaching 13 texts to the groups, the aforesaid questionnaires were administered again, together with the attitude questionnaire, to determine the impact of the intervention and to better comprehend the participants’ opinions regarding the use of DA. Results: The findings of the ANCOVA test showed that the EG outperformed the CG on the two post-tests of reading comprehension techniques and motivation. Furthermore, the findings of the one-sample t-test demonstrated that Iranian ESP university students had positive attitudes regarding DA. Conclusions: The study highlights that dynamic assessment (DA) effectively improves reading comprehension strategies and motivation among Iranian ESP students, with the experimental group outperforming the control group. Participants also expressed positive attitudes toward DA, emphasizing its potential as a valuable instructional method.